Arte contemporânea: cartografias das narrativas poéticas com crianças e adultos na escola e no museu - Santos, Núbia Agustinha Carvalho (2018)
The architecture of this thesis was constituted by five maps interspersed by a heterogeneity of theoretical lines that interfaces with the historical-cultural approach of Vygotsky (2002, 1998), which considers cultural mediation constitutive of human development; with the cartography of Deleuze-Guattari (2011a, 2010), for thinking the processes of subjectivation rhizomatically; and with the philosophy of language in Bakhtin (1995, 2011), which extends the reflection on the production of the senses from the concepts of dialogism and heteroglossia. The study also deals with the sociology of childhood, with studies by Sarmento (2008, 2004), Quinteiro (2002), Prout (2010) and other authors who provided support for understanding children's cultures and interactions among children, adults and artistic objects. The research is anchored in Costa (2012) to think the dimension of language as playful-imaginary child's creation, as a multisemiotic discursive production in the reissue of the lived; and in Salles (2004), which discusses artistic processes as unfinished gestures. This cartographic research has as one of the objectives to understand, through educational mediation, how the children of Early Childhood Education and adults give directions to the experiences with contemporary art in the school and museological spaces. The thesis was crossed by four empirical categories: educational mediation, ludic-poetic narratives, mediational flows and aesthetic experience lived in the school and in the museum. All of them interrelate in a connection made up of multiplicities of lines that intersect each other by making rhizomes. Educational mediation, being an expanded way of doing, covers the other categories in the processes of interactions. It is a potentiator of the production of artistic, cultural, sensitive and historical knowledge for all those involved in the formation process. In this thesis, it was like a scaffold in the production of sensibility and it acceded to the artistic language of children and adults to the works of contemporary art.